Odpowiedzi

2010-02-03T20:03:26+01:00
A) 2x+5y=9 / *3
-3x+4y=-2 / *2

6x+15y=27
-6x+8y=-4 / +

23y=23 / :23
y=1

2x+5=9
2x=4 / :2
x=2


B) 3x+5y=31
x+2y=12

x=12-2y
3(12-2y) + 5y=31
36-6y+5y=31
-y=-5 / :(-1)
y=5

x=12-2*5
x=12-10
x=2

C) -7x-3y=10 / *4
5x+4y=-9 / *3

-28x-12y=40
15x+12y=-27 / +

-13x=13 / :(-13)
x=-1

-7*(-1)-3y=10
-3y=3 / :(-3)
y=-1
2010-02-03T20:06:19+01:00
2x + 5y=9
-3x +4y=-2
x=2
y=1
bo
2 * 2 + 5 *1 =4+5=9
-3*2 + 4*-1 = -6 + 4= -2


2010-02-03T20:15:52+01:00
2x+5y=9
-3x+4y=-2

x=(9-5y):2
-3(9-5y):2+4y=-2

x=(9-5y):2
-13.5+7.5y+4y=-2

x=(9-5y):2
11.5y=11.5

x=(9-5y):2
y=1

x=2
y=1


3x+5y=31
x+2y=12

3x+5y=31
x=12-2y

36-6y+5y=31
x=12-2y

y=5
x=2


-7x-3y=10
5x+4y=-9

-7x-3y=10
x=(-9-4y):5

63:5+28:5-3y=10
x=(-9-4y):5

12.6+5.6-10=3y
x=(-9-4y):5

8.2=3y
x=(-9-4y):5

y=2.7
x=3.96

mam nadzieje że dobrze ale ten ostatni przykład troche dziwny